Metal toxicity and its correlation with endoplasmic reticulum stress, mitochondria functioning and gene expression analysis in occupationally exposed workers - Kumar, Durgesh; Mahdi, Abbas Ali; Ahmad, Mohammad Kaleem; Manoj, Anveshika; Prasad, Gautam; Garg, Ravindra Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Owing to the widespread presence of lead in the environment the possibility of endogenous exposure remains a serious health hazard. Lead enters in the body through inhalation and ingestion and adversely affects cells and targets the cell organelles. Methods: Aim of this study was to examine the correlation of lead toxicity with the gene expression of endoplasmic reticulum (ER) (GRP78 and PERK), mitochondrial functioning (PINK1 and PARK7), apoptosis (Pro apoptosis (BAX and p53) and anti-apoptosis (Bcl-2 and c-Myc)) in occupationally exposed painters and battery workers compared with age matched control subjects. Lead levels were measured in the whole blood by using inductively coupled plasma mass spectrometry (ICP-MS) that allow very low-level detection limit of the elements. Gene expression analysis was performed by quantitative real time PCR (qPCR). Results: Results of the study showed that the lead levels were significantly high in the painters and battery workers when compared with controls (41.37±20.71 µg/dl, 56.25±17.66 µg/dl and 6.55±2.02 µg/dl, respectively, p<0.001). Results of the gene expression analysis of ER stress, mitochondrial functioning and pro-apoptotic genes like GRP78, PERK, PINK1, PARK7, Bax and p53 were found significantly up-regulated in painters and battery workers, respectively. The Anti-apoptotic genes like Bcl-2 and c-Myc were found significantly down regulated in painters and battery workers. Conclusions: Results of the study showed that increased level of Lead alter the gene expression of ER, mitochondrial functioning and apoptosis in occupationally exposed painters and battery workers.